Gas diffusion electrode and its preparation method and application

By designing the gas diffusion electrodes of the structure of multi -layer catalytic conductive layers, the problem of insufficient stability in the existing electrode in the electrolyte of the existing electrodes in the carbon dioxide has achieved higher electrolytic performance and stability.

CN114373940BActive Publication Date: 2025-01-24TSINGHUA UNIVERSITY +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111547234.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-16
Publication Date
2025-01-24
Estimated Expiration
2041-12-16

AI Technical Summary

Technical Problem

The existing gas diffusion electrodes have poor stability during carbon dioxide electrolysis, which is difficult to meet the requirements of industrial continuous production.

Method used

Design a gas diffusion electrode with a structure of at least two layers of catalytic conductive layers. The first coating is close to the side of the gas, and the second coating is close to the side of the electrolyte. Establish a smooth transition through the quality gradient of a hydrophobic agent.

Benefits of technology

It achieves stable electrode performance under different electrolyte penetration depths, avoids sudden changes in hydrophobicity, and significantly improves the electrolysis performance and stability of carbon dioxide electrolysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114373940B_ABST
    Figure CN114373940B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of electrolytic electrodes, and in particular, to a gas diffusion electrode and a preparation method and application thereof. The gas diffusion electrode comprises a current collector and a first coating and a second coating respectively arranged on two opposite surfaces of the current collector, wherein the first coating is arranged on the surface of the current collector close to the gas side, and the second coating is arranged on the surface of the current collector close to the electrolyte side, the first coating comprises at least one catalytic conductive layer, and the second coating comprises at least one catalytic conductive layer, and each of the catalytic conductive layers is a porous structure containing a catalyst and a hydrophobic agent and capable of permeating gas; in the direction from the first coating to the second coating, the mass content of the hydrophobic agent in each of the catalytic conductive layers decreases successively.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrolytic electrodes, and in particular to a gas diffusion electrode and a preparation method and application thereof. Background Art

[0002] With the proposal of my country's carbon peak and carbon neutrality goals, carbon dioxide emission reduction technology has received increasing attention, among which carbon dioxide electroreduction is widely regarded as one of the most promising technologies. In carbon dioxide electrolysis, gas diffusion electrodes are often used to promote the mass transfer rate of the reaction and thus accelerate the reaction rate. Compared with traditional bulk electrodes, the reaction rate can be increased by more than two orders of magnitude. Most of the existing gas diffusion electrodes are based on a carbon substrate (such as commercial carbon fiber paper, carbon cloth, etc.) as the main structure, and a small amount of catalyst is further loaded on the carbon substrate. This type of commercial carbon-based electrode was originally designed and produced for hydrogen fuel cells. Its scope of application is mainly limited to the reaction process in a gas environment. During the carbon dioxide electrolysis process, the electrode needs to be in contact with a large amount of liquid, resulting in poor stability of this type of carbon-based gas diffusion electrode, mostly less than 10 hours, far below the requirements of industrial continuous production. Therefore, the current gas diffusion electrode structure is not suitable for the carbon dioxide electrolysis process. Summary of the invention

[0003] Based on this, the present invention provides a gas diffusion electrode suitable for carbon dioxide electrolysis, which has better electrolysis stability.

[0004] In one aspect, the present invention provides a gas diffusion electrode, comprising a current collector and first and second coatings respectively disposed on two opposite surfaces of the current collector, wherein the first coating is disposed on a surface close to the gas side, and the second coating is disposed on a surface close to the electrolyte side, wherein the first coating comprises at least one catalytic conductive layer, and the second coating comprises at least one catalytic conductive layer, and each of the catalytic conductive layers is a porous structure containing a catalyst and a hydrophobic agent and capable of permeating gas;

[0005] In a direction from the first coating layer to the second coating layer, the mass content of the hydrophobic agent in each of the catalytic conductive layers decreases successively.

[0006] In one embodiment, the mass percentage of the hydrophobic agent in the catalytic conductive layer of the first coating farthest from the current collector is 40% to 100%, and the mass percentage of the hydrophobic agent in the catalytic conductive layer of the second coating farthest from the current collector is not more than 30%.

[0007] In one embodiment, the mass percentage of catalyst in the catalytic conductive layer of the first coating farthest from the current collector is 5% to 40%, and the mass percentage of catalyst in the catalytic conductive layer of the second coating farthest from the current collector is 60% to 100%.

[0008] In one embodiment, the catalyst is conductive and stable at 300° C. to 360° C. without decomposition.

[0009] In one embodiment, the catalyst is one or more of a composite material of carbon and transition metal, a composite material of carbon and transition metal oxide, an alloy of noble metal and transition metal, and a composite material of noble metal and transition metal oxide, wherein the transition metal may be selected from one or more of tin, bismuth, lead, indium, and cadmium, and the noble metal may be selected from one or more of gold, silver, and platinum group metals.

[0010] In one embodiment, the preparation method of the composite material can be selected from one or more of electrodeposition, physical mixing, hydrothermal method, pyrolysis method, ball milling method, and vapor deposition method, the mass percentage of transition metal or transition metal oxide is 30% to 100%, and the mass percentage of precious metal or carbon is not more than 70%.

[0011] In one embodiment, the hydrophobic agent is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene copolymer.

[0012] In one embodiment, the content of the hydrophobic agent in each catalytic conductive layer increases sequentially from the first coating layer to the second coating layer.

[0013] In one of the embodiments, the porosity of the gas diffusion electrode is 30% to 50%.

[0014] In one embodiment, the total catalyst loading in the gas diffusion electrode is 100 mg / cm 2 Up to 250mg / cm 2 .

[0015] In another aspect, the present invention provides a method for preparing the gas diffusion electrode, comprising the following steps:

[0016] Prepare slurries containing catalyst and hydrophobic agent, and sequentially form catalytic conductive layers on two opposite surfaces of the current collector with the slurries.

[0017] wherein, in a direction from the first coating layer to the second coating layer, the mass content of the hydrophobic agent in each of the catalytic conductive layers decreases successively; and

[0018] Hole forming.

[0019] In another aspect, the present invention provides use of the gas diffusion electrode in electrolysis of carbon dioxide.

[0020] In another aspect, the present invention provides a carbon dioxide electrolysis device, comprising the gas diffusion electrode.

[0021] Compared with the prior art, the present invention has at least the following beneficial effects:

[0022] The gas diffusion electrode provided by the present invention adopts a design of at least two catalytic conductive layers, and the main components of each catalytic conductive layer are the same, which are catalysts and hydrophobic agents, ensuring that the electrode performance can remain stable at different electrolyte penetration depths; and more hydrophobic agents are added to the catalytic conductive layer located in the relatively outer layer, while relatively less hydrophobic agents are added to the catalytic conductive layer located in the relatively inner layer, so as to construct a smoothly transitioned hydrophobic capacity gradient, which is conducive to ensuring the different hydrophobicity requirements of each layer structure and avoiding the negative effects caused by the sudden change of hydrophobicity. The gas diffusion electrode provided by the present invention is particularly suitable for the electrolysis of carbon dioxide, and has excellent electrolysis performance and outstanding stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 A schematic diagram of the structure of a gas diffusion electrode prepared in Example 1;

[0025] Figure 2 A schematic diagram of the structure of a gas diffusion electrode prepared in Example 2;

[0026] Figure 3 This is a schematic diagram of the structure of the gas diffusion electrode prepared in Example 3;

[0027] Figure 4 This is a stability comparison diagram of the gas diffusion electrode prepared in Example 1 and a conventional carbon-based gas diffusion electrode;

[0028] Figure 5 This is a test performance diagram of the gas diffusion electrode prepared in Example 2;

[0029] Figure 6 This is a performance diagram of the gas diffusion electrode test prepared in Example 3. DETAILED DESCRIPTION

[0030] References to embodiments of the present invention will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present invention. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present invention without departing from the scope or spirit of the present invention. For example, a feature illustrated or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0031] Therefore, it is intended that the present invention covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present invention are disclosed in or are obvious from the following detailed description. Those of ordinary skill in the art will appreciate that this discussion is only a description of exemplary embodiments and is not intended to limit the broader aspects of the present invention.

[0032] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. For example, therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0034] The terms "comprises," "comprising," or any other variation thereof are intended to encompass non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements, but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus. In the absence of further limitations, an element defined by the phrase "comprising a ..." does not exclude the presence of additional identical elements in the process, method, article, or apparatus that includes the element.

[0035] One embodiment of the present invention provides a gas diffusion electrode, comprising a current collector and a first coating and a second coating respectively arranged on two opposite surfaces of the current collector, wherein the first coating is arranged on the surface close to the gas side, and the second coating is arranged on the surface close to the electrolyte side, the first coating comprises at least one catalytic conductive layer, and the second coating comprises at least one catalytic conductive layer, and each of the catalytic conductive layers is a porous structure containing a catalyst and a hydrophobic agent and being permeable to gas; in the direction from the first coating to the second coating, the mass content of the hydrophobic agent in each of the catalytic conductive layers decreases successively.

[0036] In the present invention, "at least one catalytic conductive layer" can be one catalytic conductive layer or two or more catalytic conductive layers. In the present invention, the outer layer and the inner layer are relative to the current collector, and are relative. For example, among the two catalytic conductive layers, the catalytic conductive layer located in the outer layer refers to the catalytic conductive layer farther away from the current collector, and the catalytic conductive layer located in the inner layer refers to the catalytic conductive layer closer to the current collector.

[0037] The gas diffusion electrode provided by the present invention adopts a design of at least two catalytic conductive layers, and the main components of each catalytic conductive layer are the same, which are catalysts and hydrophobic agents, ensuring that the electrode performance can remain stable at different electrolyte penetration depths; and more hydrophobic agents are added to the catalytic conductive layer located in the relatively outer layer, while relatively less hydrophobic agents are added to the catalytic conductive layer located in the relatively inner layer, so as to construct a smoothly transitioned hydrophobic capacity gradient, which is conducive to ensuring the different hydrophobicity requirements of each layer structure and avoiding the negative effects caused by the sudden change of hydrophobicity. The gas diffusion electrode provided by the present invention is particularly suitable for the electrolysis of carbon dioxide, and has excellent electrolysis performance and outstanding stability.

[0038] In some embodiments, the mass percentage of the hydrophobic agent in the outermost catalytic conductive layer of the first coating is 40% to 100%, and the mass percentage of the hydrophobic agent in the outermost catalytic conductive layer of the second coating is not more than 30%.

[0039] In some embodiments, the mass percentage of the catalyst in the outermost catalytic conductive layer of the first coating is 5% to 40%, and the mass percentage of the catalyst in the outermost catalytic conductive layer of the second coating is 60% to 100%.

[0040] In some embodiments, the content of the hydrophobic agent in each catalytic conductive layer increases sequentially from the first coating layer to the second coating layer.

[0041] In some embodiments, the content of the catalyst in each catalytic conductive layer decreases sequentially from the first coating layer to the second coating layer.

[0042] The gas diffusion electrode comprises at least two catalytic conductive layers, that is, the first coating comprises a catalytic conductive layer, and the second coating comprises a catalytic conductive layer.

[0043] The gas diffusion electrode may also include at least three catalytic conductive layers. In some embodiments, the first coating layer includes at least two catalytic conductive layers, and the second coating layer includes a catalytic conductive layer. In some embodiments, the first coating layer includes a catalytic conductive layer, and the second coating layer includes at least two catalytic conductive layers. In some embodiments, the first coating layer includes at least two catalytic conductive layers, and the second coating layer includes at least two catalytic conductive layers. In some specific embodiments, the gas diffusion electrode may include three catalytic conductive layers. In some embodiments, the first coating layer includes two catalytic conductive layers, and the second coating layer includes a catalytic conductive layer. In other embodiments, the first coating layer includes a catalytic conductive layer, and the second coating layer includes two catalytic conductive layers. The gas diffusion electrode also includes four catalytic conductive layers, the first coating layer includes two catalytic conductive layers, and the second coating layer includes two catalytic conductive layers. The stability of the gas diffusion electrode including at least three catalytic conductive layers is better.

[0044] The current collector of the present invention can be a metal mesh or a foam metal. The material of the metal mesh or the foam metal can be silver metal, nickel metal, titanium metal, silver alloy, nickel alloy, titanium alloy, etc. The current collector of the present invention needs to have good conductivity and relatively stable chemical properties.

[0045] In some preferred embodiments, the current collector is a titanium mesh or a silver mesh, which can improve the conductivity and alkali resistance of the electrode.

[0046] The catalyst of the present invention needs to be conductive and stable without decomposition at 300°C to 360°C.

[0047] In some embodiments, the catalyst is one or more of a composite material of carbon and transition metal, a composite material of carbon and transition metal oxide, an alloy of noble metal and transition metal, and a composite material of noble metal and transition metal oxide, wherein the transition metal may be selected from one or more of tin, bismuth, lead, indium, and cadmium, and the noble metal may be selected from one or more of gold, silver, and platinum group metals.

[0048] The preparation method of the composite material can be selected from one or more of electrodeposition, physical mixing, hydrothermal method, pyrolysis method, ball milling method and vapor deposition method.

[0049] In the composite material, the mass percentage of the transition metal or transition metal oxide may be 30% to 100%, and the mass percentage of the noble metal or carbon is not more than 70%.

[0050] In some embodiments, the hydrophobic agent is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene copolymer. In some preferred embodiments, the hydrophobic agent is polytetrafluoroethylene.

[0051] In some embodiments, the porosity of the gas diffusion electrode is 30% to 50%, which allows for better gas permeability.

[0052] In some embodiments, the total catalyst loading in the gas diffusion electrode is 100 mg / cm 2 Up to 250mg / cm 2 , excellent electrolytic performance.

[0053] The thickness of each catalytic conductive layer can be the same or different, and the thickness of each catalytic conductive layer is mainly determined by the content of catalyst in the slurry forming each catalytic conductive layer. However, preferably, the total thickness of the final gas diffusion electrode is required to be 0.2 mm to 1.0 mm.

[0054] Each catalytic conductive layer may also contain other components, such as a binder, a dispersant, etc., as well as residual pore-forming agents and decomposition products of the pore-forming agents.

[0055] The present invention further provides a method for preparing a gas diffusion electrode according to any of the above embodiments, comprising the following steps:

[0056] Prepare slurries containing catalyst and hydrophobic agent, and sequentially form catalytic conductive layers on two opposite surfaces of the current collector with the slurries.

[0057] wherein, in a direction from the first coating layer to the second coating layer, the mass content of the hydrophobic agent in each of the catalytic conductive layers decreases successively; and

[0058] Hole forming.

[0059] Each slurry can be configured by various configuration methods known to those skilled in the art. For example, the catalyst, hydrophobic agent and other components are added to the solvent and mixed. The method and order of addition are not limited by the present invention. They can be added together or in batches. Preferably, they can be mixed with the help of a mixing and degassing machine. The mixing and dispersion time is controlled within a suitable range, and the viscosity of the slurry changes by less than 5% within 10 minutes, so that it is easier to coat. Each slurry can also include other components, such as a binder, a pore-forming agent, a dispersant, etc. The solvent can be selected from various commonly used solvents in the prior art, such as N-methylpyrrolidone, dimethylformamide, dimethyl sulfoxide, tetrahydrofuran, and one or more of water and alcohols. The amount of solvent added to each slurry can be flexibly adjusted according to the viscosity and operability requirements of the slurry to be prepared.

[0060] After each slurry is prepared, it is coated on two opposite surfaces of the current collector in order from the inside to the outside and dried to form each catalytic conductive layer. The drying step is to remove components such as solvents, and the temperature can be 40-150° C. and the time can be 5 minutes to 5 hours.

[0061] The pore-forming method can be prepared by any method known in the art, such as adding a certain amount of pore-forming agent to the slurry of each catalytic conductive layer, and after the slurry is coated and dried, calcining is performed to decompose the pore-forming agent, so that each catalytic conductive layer forms a porous structure that meets the gas permeability requirements.

[0062] The types of pore-forming agents are not limited, and may include, but are not limited to, cellulose-based compounds such as hydroxyethyl methylcellulose, carboxymethyl cellulose, polyethylene glycol, polyacrylate, polyvinyl alcohol, and combinations thereof. These pore-forming agents also have a thickening effect.

[0063] Furthermore, in order to improve the hydrophobicity of the gas diffusion electrode and effectively prevent the occurrence of flooding, it further includes the step of calcining each catalytic conductive layer after coating and drying. The calcination temperature is lower than the decomposition temperature of the hydrophobic agent, but slightly higher than the melting point of the hydrophobic agent, so that the hydrophobic agent in each catalytic conductive layer is slightly melted and contacts each other to form a stable hydrophobic network structure. In some embodiments, the calcination temperature is 340°C to 360°C.

[0064] It should be noted that the step of melting the hydrophobic agent and the pore-forming process can both be carried out by a calcination process. Therefore, in the method for preparing a gas diffusion electrode of the present invention, the pore-forming step is preferably carried out by adding a pore-forming agent to the slurry and then calcining. In this way, the pore-forming step can not only ensure the porosity of each catalytic conductive layer, but also form a hydrophobic network structure at the same time.

[0065] Furthermore, the method for preparing the gas diffusion electrode of the present invention further comprises a hot pressing step. The purpose of the hot pressing step is to shape the stacked catalytic conductive layers (including the current collector), that is, to compact the stacked catalytic conductive layers, improve their mechanical strength, and at the same time improve the conductivity and adjust the electrode porosity. The hot pressing step needs to be performed before calcination.

[0066] Furthermore, the present invention also provides the use of the above-mentioned gas diffusion electrode in the electrolysis of carbon dioxide.

[0067] Furthermore, the present invention also provides a carbon dioxide electrolysis device, comprising the gas diffusion electrode.

[0068] The following are specific examples. The purpose is to further explain the present invention in detail to help the technical personnel and researchers in the field to further understand the present invention. The relevant technical conditions do not constitute any limitation to the present invention. Any form of modification made within the scope of the claims of the present invention is within the scope of protection of the claims of the present invention. The drugs and instruments used in the examples are conventionally selected in the field unless otherwise specified. The experimental methods for which specific conditions are not specified in the examples are implemented according to conventional conditions, such as the conditions described in the literature and books or the methods recommended by the manufacturer.

[0069] Example 1

[0070] (1) Preparation of the first catalytic conductive layer

[0071] Weigh 50g of pore-forming agent solution (aqueous solution of 1.8% hydroxyethyl methylcellulose by mass) and 16ml of polytetrafluoroethylene emulsion (60% by mass, water as solvent), and mix them evenly in a mixing and degassing machine. Then add 20g of catalytic active material (containing 2g of carbon black and 18g of tin oxide) to the degassing machine, and disperse them evenly again to obtain a slurry in a suitable state.

[0072] The slurry was evenly applied on one side of a titanium mesh 10 (mesh size of 100, thickness of about 0.2-0.3 mm), the thickness was controlled to be about 1.0 mm, and dried at 40° C. for 1 hour to obtain a first catalytic conductive layer 11 .

[0073] (2) Preparation of the second catalytic conductive layer

[0074] Weigh 50g of pore-forming agent solution (aqueous solution of 1.8% hydroxyethyl methylcellulose by mass) and 3ml of polytetrafluoroethylene emulsion (60% by mass, water as solvent), and mix them evenly in a mixing and degassing machine. Then add 20g of catalytic active material (containing 2g of carbon black and 18g of tin oxide) to the degassing machine and disperse them evenly again. Disperse to a suitable state to obtain a slurry.

[0075] The slurry was evenly applied on the other side of the titanium mesh 10, and the thickness of the slurry was controlled to be about 1.2 mm. The slurry was dried at 40° C. for 1 hour to obtain the second catalytic conductive layer 12.

[0076] (3) Preparation of the third catalytic conductive layer

[0077] Weigh 37.5g of pore-forming agent solution (aqueous solution of 1.8% hydroxyethyl methylcellulose by mass) and 1.5ml of polytetrafluoroethylene emulsion (60% by mass, water as solvent), and mix them evenly in a mixing and degassing machine. Then add 20g of catalytic active material (containing 2g of carbon black and 18g of tin oxide) to the degassing machine and disperse them evenly again. Disperse to a suitable state to obtain a slurry.

[0078] The slurry was evenly applied on the surface of the second catalytic conductive layer 12, with the thickness controlled to be about 0.6 mm, and dried at 40° C. for 1 hour to obtain the third catalytic conductive layer 13.

[0079] (4) Electrode forming

[0080] The stacked catalytic conductive layers obtained in steps (1) to (3) are placed on a hot press, pressed at 15 MPa and 130°C for 5 minutes, and then taken out. After cooling to room temperature, they are placed in a muffle furnace and calcined at 360°C for 15 minutes to obtain a gas diffusion electrode. The structure of the gas diffusion electrode is as follows: Figure 1 shown.

[0081] Example 2

[0082] (1) Preparation of the first catalytic conductive layer

[0083] Weigh 50g of pore-forming agent solution (aqueous solution of 1.8% hydroxyethyl methylcellulose by mass) and 16ml of polytetrafluoroethylene emulsion (60% by mass, water as solvent), and mix them evenly in a mixing and degassing machine. Then add 20g of catalytic active material (containing 2g of carbon black and 18g of tin oxide) to the degassing machine and disperse them evenly again until a suitable state is obtained to obtain a slurry.

[0084] The slurry was evenly applied on one side of a titanium mesh 10 (mesh size of 100, thickness of about 0.2-0.3 mm), the thickness was controlled to be about 1.0 mm, and dried at 40° C. for 1 hour to obtain a first catalytic conductive layer 11 .

[0085] (2) Preparation of the second catalytic conductive layer

[0086] Weigh 50g of pore-forming agent solution (aqueous solution of 1.8% hydroxyethyl methylcellulose by mass) and 3ml of polytetrafluoroethylene emulsion (60% by mass, water as solvent), and mix them evenly in a mixing and degassing machine. Then add 20g of catalytic active material (containing 2g of carbon black and 18g of tin oxide) to the degassing machine and disperse them evenly again. Disperse to a suitable state to obtain a slurry.

[0087] The slurry was evenly applied on the other side of the titanium mesh 10, and the thickness of the slurry was controlled to be about 1.2 mm. The slurry was dried at 40° C. for 1 hour to obtain the second catalytic conductive layer 12.

[0088] (3) Electrode forming

[0089] The stacked catalytic conductive layers obtained in steps (1) to (2) are placed on a hot press, pressed at 15 MPa and 130°C for 5 minutes, and then taken out. After cooling to room temperature, they are placed in a muffle furnace and calcined at 360°C for 15 minutes to obtain a gas diffusion electrode. The structure of the gas diffusion electrode is as follows: Figure 2 shown.

[0090] Example 3

[0091] (1) Preparation of the first catalytic conductive layer

[0092] Weigh 50g of pore-forming agent solution (aqueous solution of 1.8% hydroxyethyl methylcellulose by mass) and 16ml of polytetrafluoroethylene emulsion (60% by mass, water as solvent), and mix them evenly in a mixing and degassing machine. Then add 20g of catalytic active material (containing 2g of carbon black and 18g of tin oxide) to the degassing machine and disperse them evenly again until a suitable state is obtained to obtain a slurry.

[0093] The slurry was evenly applied on one side of a titanium mesh 10 (mesh size of 100, thickness of about 0.2-0.3 mm), the thickness was controlled to be about 1.0 mm, and dried at 40° C. for 1 hour to obtain a first catalytic conductive layer 11 .

[0094] (2) Preparation of the second catalytic conductive layer

[0095] Weigh 50g of pore-forming agent solution (aqueous solution of 1.8% hydroxyethyl methylcellulose by mass) and 3ml of polytetrafluoroethylene emulsion (60% by mass, water as solvent), and mix them evenly in a mixing and degassing machine. Then add 20g of catalytic active material (containing 2g of carbon black and 18g of tin oxide) to the degassing machine and disperse them evenly again. Disperse to a suitable state to obtain a slurry.

[0096] The slurry was evenly applied on the other side of the titanium mesh 10, and the thickness of the slurry was controlled to be about 1.2 mm. The slurry was dried at 40° C. for 1 hour to obtain the second catalytic conductive layer 12.

[0097] (3) Preparation of the third catalytic conductive layer

[0098] Weigh 37.5g of pore-forming agent solution (aqueous solution of 1.8% hydroxyethyl methylcellulose by mass) and 1.5ml of polytetrafluoroethylene emulsion (60% by mass, water as solvent), and mix them evenly in a mixing and degassing machine. Then add 20g of catalytic active material (containing 2g of carbon black and 18g of tin oxide) to the degassing machine and disperse them evenly again. Disperse to a suitable state to obtain a slurry.

[0099] The slurry was evenly applied on the surface of the second catalytic conductive layer 12, with the thickness controlled to be about 0.6 mm, and dried at 40° C. for 1 hour to obtain the third catalytic conductive layer 13.

[0100] (4) Preparation of the fourth catalytic conductive layer

[0101] Weigh 50g of pore-forming agent solution (aqueous solution of 1.8% hydroxyethyl methylcellulose by mass) and 18ml of polytetrafluoroethylene emulsion (60% by mass, water as solvent), and mix them evenly in a mixing and degassing machine. Then add 20g of catalytic active material (containing 2g of carbon black and 18g of tin oxide) to the degassing machine and disperse them evenly again. The slurry is obtained in a suitable state.

[0102] The slurry is evenly applied on the surface of the first catalytic conductive layer 11 with a thickness of about 1.0 mm, and dried at 40° C. for 1 h to obtain the fourth catalytic conductive layer 14 .

[0103] (5) Electrode forming

[0104] The stacked catalytic conductive layers obtained in steps (1) to (4) are placed on a hot press, pressed at 15 MPa and 130°C for 5 minutes, and then taken out. After cooling to room temperature, they are placed in a muffle furnace and calcined at 360°C for 15 minutes to obtain a gas diffusion electrode. The structure of the gas diffusion electrode is as follows: Figure 3 shown.

[0105] Test Case

[0106] The gas diffusion electrodes prepared in Examples 1 to 3 were used as cathode electrodes, carbon paper loaded with iridium oxide catalyst was used as anode electrodes, potassium bicarbonate solution was used as electrolyte, and DuPont Nafion 211 was used as cation exchange membrane to assemble an electrolysis device. -2 Under the conditions of , the electrolysis voltage was 3.05V, the energy efficiency reached about 45%, and the stability of the cathode electrode in each electrolysis device was measured. During the electrolysis time of more than 500 hours, the performance of the cathode electrode did not decay, and the Faraday efficiency of the product formic acid remained above 80%, showing excellent stability. In contrast, the traditional carbon-based gas diffusion electrode (Sigracet 29BC) has a shorter stabilization time, and the electrode was flooded in less than 3 hours. The stability of the gas diffusion electrodes prepared in Example 2 and Example 3 is also significantly better than that of the traditional carbon-based gas diffusion electrodes. Similarly, at a current density of 200mA / cm -2 Under the conditions of , the voltage can be kept stable for more than 300 hours and 400 hours of electrolysis time respectively, and the formic acid Faradaic efficiency is maintained above 80%. Figure 4 , Figure 5 , Figure 6 The test results of electrolysis devices assembled using the gas diffusion electrodes prepared in Example 1, Example 2, and Example 3 as cathode electrodes are shown respectively.

[0107] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0108] The above-described embodiments only express several implementation methods of the present invention, which are convenient for understanding the technical solutions of the present invention in detail, but they cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided by the present invention are all within the protection scope of the claims attached to the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the contents of the attached claims, and the description and drawings can be used to explain the contents of the claims.

Claims

1. A gas diffusion electrode, characterized in that: It comprises a current collector and a first coating and a second coating respectively arranged on two opposite surfaces of the current collector, the current collector is a metal mesh or a foamed metal, the first coating is arranged on the surface of the current collector close to the gas side, the second coating is arranged on the surface of the current collector close to the electrolyte side, the first coating comprises at least one catalytic conductive layer, the second coating comprises at least one catalytic conductive layer, each of the catalytic conductive layers is a porous structure containing a catalyst and a hydrophobic agent and being permeable to gas, the catalyst is a composite material of carbon and a transition metal oxide, and the transition metal oxide is tin oxide; The gas diffusion electrode is suitable for carbon dioxide electrolysis, the Faraday efficiency of formic acid produced by the carbon dioxide electrolysis of the gas diffusion electrode is above 80%, the gas diffusion electrode comprises at least three catalytic conductive layers, and the mass content of the hydrophobic agent in each of the catalytic conductive layers decreases in sequence from the first coating layer to the second coating layer; The porosity of the gas diffusion electrode is 30% to 50%.

2. The gas diffusion electrode according to claim 1, characterized in that The mass percentage of the hydrophobic agent in the catalytic conductive layer of the first coating layer farthest from the current collector is 40% to 100%, and the mass percentage of the hydrophobic agent in the catalytic conductive layer of the second coating layer farthest from the current collector is not more than 30%.

3. The gas diffusion electrode according to claim 1, characterized in that The mass percentage of catalyst in the catalytic conductive layer of the first coating layer farthest from the current collector is 5% to 40%, and the mass percentage of catalyst in the catalytic conductive layer of the second coating layer farthest from the current collector is 60% to 100%.

4. The gas diffusion electrode according to claim 1, characterized in that The catalyst is conductive and stable at 300° C. to 360° C. without decomposition.

5. The gas diffusion electrode according to claim 4, characterized in that The first coating layer includes one catalytic conductive layer, and the second coating layer includes two catalytic conductive layers.

6. The gas diffusion electrode according to claim 1, characterized in that The hydrophobic agent is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene copolymer.

7. The gas diffusion electrode according to claim 1, characterized in that In a direction from the first coating layer to the second coating layer, the content of the hydrophobic agent in each catalytic conductive layer increases successively.

8. The gas diffusion electrode according to any one of claims 1 to 4 and 6 to 7, characterized in that: The gas diffusion electrode comprises three or four catalytic conductive layers.

9. The gas diffusion electrode according to any one of claims 1 to 7, characterized in that: The total catalyst loading in the gas diffusion electrode is 100 mg / cm 2 Up to 250mg / cm 2 .

10. The method for preparing a gas diffusion electrode according to any one of claims 1 to 9, characterized in that: The following steps are involved: Prepare slurries containing catalyst and hydrophobic agent, and sequentially form catalytic conductive layers on two opposite surfaces of the current collector with the slurries. wherein, in a direction from the first coating layer to the second coating layer, the mass content of the hydrophobic agent in each of the catalytic conductive layers decreases successively; and Hole forming.

11. Use of the gas diffusion electrode according to any one of claims 1 to 9 in electrolysis of carbon dioxide.

12. A carbon dioxide electrolysis device, characterized in that: It comprises the gas diffusion electrode according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Structure of direct alcohol fuel cell membrane electrode aggregate and preparation method thereof

    CN102005582A

  • Stable air electrode of zinc-air battery

    CN102738472A

  • Metal-air battery cathode and preparation method thereof

    CN109888299A

  • Gas diffusion electrode for reducing carbon dioxide

    CN110770370A